The Dry Puna as an ecological megapatch and the peopling of South America: Technology, mobility, and the development of a late Pleistocene/early Holocene Andean hunter-gatherer tradition in northern Chile - Osorio, Daniela; Steele, James; Sepulveda, Marcela; Gayo, Eugenia M.; Capriles, Jose M.; Herrera, Katherine; Ugalde, Paula; De Pol Holz, Ricardo Hernán; Latorre, Claudio; Santoro, Calogero M. (My University, 2017)
Current scientific evidence shows that humans colonized South America at least 15,000 years ago, but there are still many unknown aspects of this process, including the major and minor migratory routes involved, and the pattern of successive occupation of a diverse continental mosaic of ecosystems. In this context, the role of the Andean highlands (>= 3400 meters above sea level) has been neglected, because of the supposedly harsh conditions for humans including hypoxia and cold climate. Nevertheless, the environmental and cultural resources available in the high Andes constitutes an important "megapatch" that should be assessed in terms of human settlement patterns. We review the evidence for late Pleistocene/early Holocene hunter-gatherer occupation of one part of this megapatch, the northern Chilean Dry Puna, in its palaeoecological context. We focus on lithic technology, faunal remains, radiocarbon dates, and other archaeological materials related to different social activities, which allow us to suggest that groups of hunter-gatherers organized and adapted their way of life to highland ecosystems through logistical mobility, and curatorial strategies for lithic tool kits that included projectile points and other formalized tools. The morphology and technological processes involved are recognized over vast territories along the high Andes. We identify this material expression as the high south central Andean Archaic hunter-gatherer tradition, which also featured long distance mobile settlement systems and communication processes over this broad and distinct megapatch. More speculatively, we outline the hypothesis that these highland ecosystems constituted a suitable migratory route that may have been key for the early peopling of the continent, and contrast it with the alternative hypothesis of the initially secondary and seasonally intermittent exploitation of this habitat by hunter-gatherers dispersing along the Pacific coastal corridor. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.
Keywords: early peopling of south america; south central andean archaic; dry puna; high andes; late pleistocene; megapatch